Peptídeos cíclicos hepatotóxicos: MALDI-TOF como uma ferramenta analítica - Sandonato, Beatriz Brabetz [UNESP] (2014)
Cyanobacteria are photosynthetic bacteria that can be found in diverse environments. Some species of cyanobacteria produce toxins denominated cyanotoxins. The cyanotoxins called microcystins (MCs) are hepatotoxic cyclic heptapeptides produced during cyanobacterial blooms. Its detection and quantification in springs are of great importance due to damage to human health that these microcystins can cause. Currently, MALDI-TOF-MS technique has been shown to be an efficient tool for the analysis of microcystins, and recent studies have reported its use in the quantification of these. On the exposed, the aim of this thesis was to evaluate the different matrices and different methods of sample preparation for MALDI-MS aimed at the detection and quantification of microcystins. With the aim of achieving the best method of quantification of microcystins nine matrices for MALDI eleven methods of sample preparation over a method that was adapted by our research group, the adapted vacuum drying method, and two commercial standards of microcystins, MC-LR, and MC-RR, are used. The evaluation methods of sample preparation was performed using as matrix the α- cyano-4-hydroxycinnamic acid (CHCA) and the angiotensin I as internal standard. The methods were evaluated with respect to their coefficients of variation (CV), their crystallization and spectra obtained using the MC-RR as a sample. The adapted vacuum drying method showed the best results and their analytical curve was constructed using both variants of microcystins. The limit of detection (MDL) and the limit of quantification (LOQ) were also calculated. Each curve variant of microcystin showed excellent linearity and r values ranged from 0.98 to 99, showing that the method is suitable for quantifying these. After analysis of the methods of sample preparation, the nine matrices were evaluated with respect to CV, crystallization and spectra, using the MC-RR as a sample. The best results were obtained...